2006
DOI: 10.1002/jcu.20201
|View full text |Cite
|
Sign up to set email alerts
|

Color and power Doppler sonography of extracranial and intracranial arteries in moyamoya disease

Abstract: Transcranial CD and PD can be used to demonstrate the stenosis and occlusion of intracranial arteries and the abnormal vascular network at the base of the brain in most cases. Combined with the hemodynamic characteristics of extracranial arteries and the symptoms of the patients, an accurate diagnosis of moyamoya disease could be made in the majority of cases using PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…MMD is characterized by progressive stenosis of the bilateral terminal portions of internal carotid arteries, and their main branches, resulting in increased resistance in the distal vessel and decreased velocity and blood ow volume in the proximal vessel. Ruan et al showed that the time-averaged mean ow velocity of ICA in MMD patients was lower than that in normal controls, and the RI was higher than that in normal controls [25]. Our ndings seemed to be consistent with previous studies, our results showed that as the Suzuki stage advanced, the PSV, EDV and FV of EICA decreased.…”
Section: Discussionsupporting
confidence: 92%
“…MMD is characterized by progressive stenosis of the bilateral terminal portions of internal carotid arteries, and their main branches, resulting in increased resistance in the distal vessel and decreased velocity and blood ow volume in the proximal vessel. Ruan et al showed that the time-averaged mean ow velocity of ICA in MMD patients was lower than that in normal controls, and the RI was higher than that in normal controls [25]. Our ndings seemed to be consistent with previous studies, our results showed that as the Suzuki stage advanced, the PSV, EDV and FV of EICA decreased.…”
Section: Discussionsupporting
confidence: 92%
“…Tortuosity of cerebral arteries has been reported for aged, hypertensive patients [5,23,24,69] and in patients with ‘Moyamoya’ disease [70,71,72]. Cerebral arteries may also become tortuous due to malformation [73] or increased flow [34,35] associated with elastin degradation.…”
Section: Etiology: Association With Vessel Diseases and Clinical Consmentioning
confidence: 99%
“…There are several studies confirming the potential of trans cranial power Doppler and color Doppler ultrasonography in the detection of arteries that appear occluded on DS angiography 72 or on MR angiography. 2,14,47 According to some authors, 73 ultrasonography was also able to reveal alterations of vessels that appear normal on angiography, while at the same time not all angiographic features could be found on ultrasound studies.…”
Section: The Ultrasonography Modalitymentioning
confidence: 97%
“…72 Compared with the color Doppler method, power Doppler is relatively independent from the insonation angle, is not subject to aliasing, and is associated with relatively low background noise, thus offering an increase in sensitivity of approximately 10-15 dB. This accounts for the good sensitivity in the detection of low-flow areas and of parts of the intracranial collateral network, 55,72 with a spatial resolution > 1 mm. It has been described as a valid method for diagnosis 73 and for the evaluation of direct (bypass patency) and indirect (neoangiogenesis) revascularization, with a good interobserver agreement for a 3-grade scale.…”
Section: The Ultrasonography Modalitymentioning
confidence: 99%